Evaluating the emotional bidding framework: new evidence from a decade of neurophysiology - Marc T. P. Adam; Jan Krämer (Electronic Markets, 2022)
Ten years ago the "emotional bidding framework" (Adam et al.,~ Electronic Markets, 21 (3), 197–207, 8 ) was published in this journal. It provided a conceptualization for the role of human emotion in electronic auctions along six propositions on how emotions emerge during the auction process and affect auction outcomes. While the framework emphasized the importance of immediate emotional responses and momentary changes in the bidders' emotional state, the original article did not include an evaluation of its propositions given the limited data on how bidders experience emotions in the moment that they occur. Ten years on, advances in the growing research field of NeuroIS allow to evaluate the propositions based on neurophysiological evidence. As a rejoinder of the original article, the present paper synthesizes these insights, refines the framework further, and identifies fruitful areas for future research based on remaining gaps in the body of knowledge.
Keywords: D44; L81; 620; Auctions; Auction Fever; NeuroIS